IMPLEMENTASI KEGIATAN PRAMUKA UNTUK MENINGKATKAN KECERDASAN INTERPERSONAL DEWAN PENGGALANG DI MTs THORIQUL HUDA CATAK GAYAM MOJOWARNO JOMBANG - M. Wafiul Ahdi; Moch. Ansor (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The objective of this research "Implementation of Scout Activities to Increase Students' Interpersonal Intelligence at MTs Thoriqul Huda Catakgayam Mojowarno Jombang". This research was conducted because the researcher saw that each student actually has potential and abilities in their respective fields and each potential can be developed, one of which is through scout activities. So far, researchers have read that scouts have an influence that can foster students' interpersonal intelligence. However, we ourselves do not know how the process of planning, implementing and evaluating scout activities is, so this research will also focus on these 3 things, namely planning, implementation and evaluation. Meanwhile, the aim is to understand the 3 focuses of the discussion above. This research uses a field research method that uses a qualitative descriptive approach. Researchers conducted interviews with subjects, namely the Head of the Madrasah, Scoutmaster and 2 Students at MTs Thoriqul Huda Catakgayam. After conducting observations, interviews and documentation, the researchers found that the planning, implementation and evaluation of scout activities contained social sensitivity, social insight and social communication in accordance with the components of interpersonal intelligence. The conclusion of this research is that Scout activities contribute significantly to developing students' interpersonal intelligence, so it is recommended that they continue to be improved and made part of character development strategies in the school environment.